1980
DOI: 10.1128/aac.17.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between the induction of potassium efflux and cytostatic activity of polyene macrolides in mammalian cells

Abstract: The paper contains data on the induction of K+ efflux and viability of baby hamster kidney (BHK-21) cells after their treatment with macrolide antibiotics inducing specific pores in membrane. New water-soluble semisynthetic derivatives of amphotericin B and aureofacin (N-glycosyl and trimethylammonium methyl ester derivatives) as well as the parent compounds were used to compare the concentration of antibiotics inducing permeabilizing and cytostatic effects. We found that a two-to eight-times-higher concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…This observation was supported later by other investigators using Chlorella vulgaris (2,4,17), Candida albicans (5), Histoplasma capsulatum (1), and animal cells grown in vitro (13,19 The main pharmacological utility of polyenes is based primarily on the quantitative differences in the affinity of these antibiotics for ergosterol and cholesterol in fungal (pathogen) and mammalian (host) cell membranes, respectively (11); therefore, polyene macrolide treatment affects the pathogen as well as the host. It is important to determine and find differential conditions in which host cells can recover from polyene treatment while pathogenic organisms are inhibited or killed.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…This observation was supported later by other investigators using Chlorella vulgaris (2,4,17), Candida albicans (5), Histoplasma capsulatum (1), and animal cells grown in vitro (13,19 The main pharmacological utility of polyenes is based primarily on the quantitative differences in the affinity of these antibiotics for ergosterol and cholesterol in fungal (pathogen) and mammalian (host) cell membranes, respectively (11); therefore, polyene macrolide treatment affects the pathogen as well as the host. It is important to determine and find differential conditions in which host cells can recover from polyene treatment while pathogenic organisms are inhibited or killed.…”
supporting
confidence: 68%
“…This observation was supported later by other investigators using Chlorella vulgaris (2,4,17), Candida albicans (5), Histoplasma capsulatum (1), and animal cells grown in vitro (13,19). However, the nature of the repair of membrane alterations, as well as essential factors influencing this process, remains unknown.…”
supporting
confidence: 67%
“…The superiority of the non-sterol-containing composition in vitro could be due to the ability of such liposomes to remove cholesterol from the cell membrane (9), thus making the cell less sensitive to the effects of amphotericin B. Whether a similar result would be observed in other in vitro toxicity tests such as K+ efflux measurements (22,23) or erythrocyte hemolysis (26) is not known. However, it is clear that the tissue culture cytotoxicity test cannot replace the in vivo assay for predicting the lethal dose response to liposomal amphotericin B.…”
Section: Discussionmentioning
confidence: 92%
“…Our results for both the deoxycholate and liposome amphotericin B agree with those of previous studies. Others have shown that, after 24 h of incubation, the growth of baby hamster kidney cells was significantly reduced by 5 ,ug and totally inhibited by 15 ,ug of amphotericin B per ml as the deoxycholate dispersion (22). For L-929 and HeLa cells, viability was decreased after a 2-h incubation with 40 p,g of Fungizone per ml as assessed by trypan blue exclusion (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation